The Influence of Perception of Usefulness and Perception of Ease on The Intention of Using QRIS by Accounting Students of Politeknik Negeri Tanah Laut - Pertiwi, Fidia Ramadhani Putri; Suasri, Eni; Suwarno, Try Edi; Bandi, Maulida Hirdianti (Quantitative Economics and Management Studies, 2025)
This study aims to analyze the effect of perception of usefulness and perception of ease of use on the intention to use QRIS by Accounting students of Politeknik Negeri Tanah Laut. Using multiple linear regression method, this study involved 318 students as respondents. The results showed that perception of usefulness had a significant effect on the intention to use QRIS (p < 0.05), while perception of ease also showed a significant effect. Simultaneously, these two variables contributed 47.3% to the intention to use QRIS. This finding indicates the importance of increasing awareness of the benefits and ease of use of QRIS to encourage the adoption of digital payment systems among students. This study is expected to be a reference for policy development and further research on digital payment technology.